(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This thesis highlights the significance of digital storytelling as a modern pedagogical tool for improving English pronunciation skills among secondary school students. Traditional methods, often based on drilling and repetition, may not sufficiently motivate learners or provide meaningful contexts for practice. The study emphasizes that the integration of digital stories into language teaching creates opportunities for students to practice phonetic accuracy, stress, and intonation through recording their voices, creating narratives, and presenting them in digital formats. Such an approach not only enhances pronunciation but also boosts students’ confidence, creativity, and motivation in the learning process.